CAMP-Dependent Calcium Oscillations of Astrocytes: An Implication for Pathology. (22nd January 2016) - Ujita, Sakiko; Sasaki, Takuya; Asada, Akiko; Funayama, Kenta; Gao, Mengxuan; Mikoshiba, Katsuhiko; Matsuki, Norio; Ikegaya, Yuji
Abstract: Astrocytes in various brain regions exhibit spontaneous intracellular calcium elevations both in vitro and in vivo; however, neither the temporal pattern underlying this activity nor its function has been fully evaluated. Here, we utilized a long-term optical imaging technique to analyze the calcium activity of more than 4000 astrocytes in acute hippocampal slices as well as in the neocortex and hippocampus of head-restrained mice. Although astrocytic calcium activity was largely sparse and irregular, we observed a subset of cells in which the fluctuating calcium oscillations repeated at a regular interval of ∼30 s. These intermittent oscillations i) depended on type 2 inositol 1, 4, 5-trisphosphate receptors; ii) consisted of a complex reverberatory interaction between the soma and processes of individual astrocytes; iii) did not synchronize with those of other astrocytes; iv) did not require neuronal firing; v) were modulated through cAMP-protein kinase A signaling; vi) were facilitated under pathological conditions, such as energy deprivation and epileptiform hyperexcitation; and vii) were associated with enhanced hypertrophy in astrocytic processes, an early hallmark of reactive gliosis, which is observed in ischemia and epilepsy. Therefore, calcium oscillations appear to be associated with a pathological state in astrocytes.